THE EFFECT OF SOAKING ARECA NUT (Areca catechu Linn.) SEED EXTRACT ON THE SURFACE ROUGHNESS OF NANOHYBRID COMPOSITE RESIN IN-VITRO STUDY - Soraya Tanjung, Dian; Daryono; Tsalasuna R, Azka (Journal of Health and Dental Sciences, 2026)
The habit of chewing betel quid in the community is based on the belief that its consumption can strengthen teeth. However, this practice may have an impact on the dental restorative materials used. Nanohybrid composite resin is one of the restorative materials widely applied in current dental practice. This study was conducted to determine the effect of immersion in areca nut seed extract on the surface roughness of nanohybrid composite resin. This research was an experimental laboratory study with a pre-test and post-test group design. A total of 30 nanohybrid composite resin specimens were used as research samples and divided into three treatment groups, each of which was immersed in areca nut seed extract at concentrations of 2%, 4%, and 6%. Surface roughness was measured using a Surface Roughness Tester, while data analysis was performed using the Wilcoxon statistical test. The results showed that the mean surface roughness values of nanohybrid composite resin before immersion in areca nut seed extract at concentrations of 2%, 4%, and 6% were 0.187±0.015, 0.192±0.014, and 0.202±0.016, respectively. After immersion, the surface roughness values increased to 0.362±0.055, 0.383±0.048, and 0.403±0.019. The Wilcoxon test indicated a statistically significant difference in surface roughness values before and after immersion in areca nut seed extract (p = 0.005; p < 0.05). Based on these findings, it can be concluded that immersion in areca nut seed extract at concentrations of 2%, 4%, and 6% has a significant effect on increasing the surface roughness of nanohybrid composite resin (p < 0.05). DOI : 10.54052/jhds.v5n3.p233-242